7x + 3y = -25

-7x + 9y = -47 (1 point)

1 answer

To solve this system of linear equations, we can use the method of elimination.

First, let's multiply the first equation by 7 and the second equation by 1 to eliminate the x terms:

(7) * (7x + 3y) = (7) * (-25)
49x + 21y = -175

(1) * (-7x + 9y) = (1) * (-47)
-7x + 9y = -47

Now we can add the two equations together to eliminate the x terms:

49x + 21y - 7x + 9y = -175 - 47
42y = -222
y = -222 / 42
y = -37 / 7
y = -6

Now that we have found the value of y, we can substitute it back into one of the original equations to solve for x. Let's use the first equation:

7x + 3(-6) = -25
7x - 18 = -25
7x = -7
x = -7 / 7
x = -1

Therefore, the solution to the system of equations is x = -1 and y = -6.